Comparing the efficacy of integrated and face-to-face education based on self-regulation on students\' self-efficacy - zeinab barzgar zarmehri; jahanshir tavakoli zadeh; majid pakdaman (مجله علوم روانشناختی)
Background: The implementation of self-regulated learning plays a role in reducing students' anxiety and increasing the level of deeper information processing in them. Among the applications of education based on self-regulation is its role in increasing students' self-efficacy, which has received less attention from researchers so far. There is a research gap regarding the effectiveness of integrated education based on self-regulation on students' self-efficacy. Aims: This research was conducted with the aim of comparing the efficacy of the integrated and face-to-face education program based on self-regulation on the self-efficacy of sixth grade elementary School female students. Methods: The method of the current research was semi-experimental with a pre-test-post-test design with a control group. The statistical population of the research included all sixth grade elementary School female students of Qaenat city in the academic year of 2022-2023. 54 students were selected from among the students of the statistical community using convenience sampling method, And they were randomly assigned in two experimental groups (18 people in the integrated training group based on self-regulation, 18 people in the face-to-face training group based on self-regulation) and a control group (18 people). The data collection tool in this research was the self-efficacy questionnaire (Sherer et al., 1982). Integrated training sessions (researcher-made) were held in 8 weeks for the first experimental group, and face-to-face training group sessions were held in 7 weeks for the second experimental group. Analysis of the research data was done using covariance analysis method and using SPSS-24 software. Results: The results showed that there is a significant difference between the effectiveness of two methods of integrated and face-to-face education based on self-regulation on students' self-efficacy, And integrated training is more effective than face-to-face training in increasing self-efficacy (P< 0.01). In addition, the average of both integrated and face-to-face education groups was more effective on students' self-efficacy than the control group (P< 0.01). Conclusion: According to the findings of the present research on the greater effectiveness of integrated education based on self-regulation on the self-efficacy of elementary school students, The use of this educational method is suggested to educational psychologists, school counselors and all officials in the field of education.